FORMATION OF LINGUISTIC COMPETENCE OF FUTURE ECONOMIES IN PROFESSIONAL PREPARATION - Богославець, Л. О.; Кікена, Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
In the article, on the example of the functioning of some specialized programs, features of the formation of skills of speech competence of future economists are analyzed. It is proved that the level of professionalism of a specialist determines the competence, and his achievements are due to the necessary competencies, the latter are achieved in the process of training. The purpose and result of professional training of a specialist is the level of competence formation. The role of language competence in shaping the professional and general culture of future specialists, the influence of her and linguistic culture on the general intellectual development of modern youth is revealed. It is proved that linguistic education of a future economist is an important factor in his readiness for active intellectual activity in the information space. The meaning of the definition of "competence" is clarified. Based on the generalization of literary sources, the structure of professional competence of future economists and its components is determined. It is proved that for the implementation of all economic operations within the limits of this competence, a young specialist-economist should first of all master the professional terminology, that is, be fluent in competence. Recommendations for the further improvement of Ukrainian business language curricula for e-students are developed on the basis of comparative analysis of the methods of forming language competence in higher education institutions